Corruption News in Online Media Post Amendment of the 2019 Corruption Eradication Commission Law - Riswandi, Riswandi; Pambayun, Ellys Lestari; Nugraha, Rahmadya Putra (Jurnal Kajian Jurnalisme, 2021)
The process of the new commissioner election and the amendment to the Corruption Eradication Commission (KPK) received public attention due to the controversial agenda and arguably had weakened the KPK. The purpose of this study is to describe the discourse of Kompas.com, CNN Indonesia, and Republika.co.id regarding corruption after the amendment of the KPK law using Teun Van Dijk's critical discourse method and news text analysis unit from 21 December 2019-29 February 2020. The results found that at the level of macro structure, superstructure, and micro structure, the three online media discourse advocacy and support for the KPK and criticism of Joko Widodo's government in detail, systematically, and with minimal lexicons and metaphors, and represent public aspirations for the KPK as an independent institution in eradicating corruption. The results on the macro, superstructure, and micro-level showed that Kompas.com established defense and support discourse to the Commission to Eradicate Criminal Acts of Corruption through detailed, systematic reporting, without lexicons and metaphors. Contrastingly, CNN Indonesia emphasized on the facts of real actions taken by the Corruption Eradication Commission in combating corruption and the amount of losses. Moreover, Republika.co.id emphasized on the weakness in the revised law of the KPK and reinforces its hypothesis of the news with the proper metaphor.